Republic of Congo : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The key issue facing Congo is how to use oil and mineral resources effectively in support of inclusive growth. Economic conditions are supportive--macroeconomic stability is in place, the terms of trade are favorable, and the external position is strong. External risks are mitigated by membership in CEMAC, under which all members benefit from the French convertibility guarantee, and large fiscal buffers. Yet, growth has not been inclusive. Over half of the population lives in poverty and a labor skills mismatch results in high unemployment and underemployment, especially among youth. The difficult business climate holds back diversification. On March 4, 2012 a munitions depot exploded in Brazzaville causing death and destruction; near-term policies focus on reconstruction and addressing the humanitarian crisis.